Impact of the construction of the Container Terminal (APM Terminals) in Moín Beach, Costa Rica - Vargas-Hernández, Annie (2018)
This research is based the analysis that the effect that the construction of the Container Terminal of Moín (TCM) had on the beach from the beginning of the work until 2017. The impact is determined by the effects on changes in the coastline and the profile of the beach. The results showed a regression of the coastline before the construction, which has been extended with the TCM and that the biggest changes are due to the interruption of the sediment transport currents and the artificial accretion of the beach, in the vicinity of the TCM.